Formulation Development of Verapamil Hydrochloride Tablet by Effervescent Method - Kabir, Abul Kalam Lutful; Huda, Naz Hasan; Jhanker, Yeakuty Marzan; Shamin, Kamrunnahar (Stamford Journal of Pharmaceutical Sciences, 2011)
Fast disintegrating tablets of Verapamil Hydrochloride were designed to achieve increased absorption as well as quick onset of pharmacological action of the active ingredient with a view to enhance patient compliance by effervescent method. Different combinations and ratios of sodium bicarbonate, anhydrous citric acid, sodium starch glycolate, Micro-crystalline cellulose (MCC) and lactose were used in order to get optimum result. The prepared formulations were evaluated for hardness, friability, thickness, diameter, taste of the solution to be administered and in-vitro dispersion time. The acceptable dispersion time was achieved by using a combination of citric acid and sodium bi carbonate in the same amount along with sodium starch glycolate, micro-crystalline cellulose (MCC) & lactose. Acceptable taste of the solution to be administered was obtained with a combination of sucrose, aspartame and sodium saccharine. Key words: Effervescent method; Verapamil Hydrochloride; Dispersion time DOI: 10.3329/sjps.v3i1.6795 S. J. Pharm. Sci. 3(1): 34-37